The economics of greening the Grahamstown National Arts Festival in South Africa - Blaise Dobson; Jen Snowball (Acta Academica, 2012)
The article analyses the broad history underpinning the notion of sustainable development and its context within the events industry in South Africa. It explores the willingness of festival-goers to pay for a hypothetical recycling programme to reduce the negative externalities of the Festival. Results show that festival-goers were, on average, willing to pay an additional R2.30 per “green” ticket to fund the proposed programme. A statistical regression was used to explore the determinants of willing-to-pay. If applied to all tickets, the total willing-to-pay amount far exceeded the actual cost of the recycling programme.